Development of a simple, accurate SPME-based method for assay of VOCs in column breakthrough experiments. - Salaices Avila, Manuel Alejandro; Breiter, Roman; Mott, Henry (Chemosphere, 2007)
Solid-phase microextraction (SPME) with gas chromatography is to be used for assay of effluent liquid samples from soil column experiments associated with VOC fate/transport studies. One goal of the fate/transport studies is to develop accurate, highly reproducible column breakthrough curves for 1,2-cis-dichloroethylene (cis-DCE) and trichloroethylene (TCE) to better understand interactions with selected natural solid phases. For SPME, the influences of the sample equilibration time, extraction temperature and the ratio of volume of sample bottle to that of the liquid sample (V(T)/V(w)) are the critical factors that could influence accuracy and precision of the measured results. Equilibrium between the gas phase and liquid phase was attained after 200 min of equilibration time. The temperature must be carefully controlled due to variation of both the Henry's constant (K(h)) and the fibre/gas phase distribution coefficient (K(fg)). K(h) decreases with decreasing temperature while K(fg) increases. Low V(T)/V(w) yields better sensitivity but results in analyte losses and negative bias of the resultant assay. High V(T)/V(w) ratio yields reduced sensitivity but analyte losses were found to be minimal, leading to better accuracy and reproducibility. A fast SPME method was achieved, 5 min for SPME extraction and 3.10 min for GC analysis. A linear calibration function in the gas phase was developed to analyse the breakthrough curve data, linear between a range of 0.9-236 microgl(-1), and a detection limit lower than 5 microgl(-1).